Modeling of COVID-19 Growth Cases in Bandung Regency and Bandung City Using Vector Autoregression - Megantara, Tubagus Robbi; Hidayana, Rizki Apriva; Syarifudin, Abdul Gazir; Amelia, Rika; Nurkholipah, Nenden Siti (iora, 2024)
COVID-19 is a global health epidemic due to increasing infections and deaths. Indonesia has many confirmed cases with high daily case growth, including the Bandung City and Bandung Regency areas. High mobility between regions can impact the growth of COVID-19 cases. Strategies to prevent the growth of COVID-19 cases need to be carried out by considering the growth of COVID-19 cases in the nearest area. The Vector Autoregression (VAR) model is a forecasting model that can consider geographic impacts. This study aims to model the growth of cases in adjacent areas and have high mobility using the VAR method. The growth of COVID-19 cases in Bandung City and Bandung Regency is integrated into the VAR model to see the impact of each other. The VAR model also considers the impact of case growth in the past on its region's future. Transformation and differencing are carried out on the time series of case growth in each region to achieve time-series stationarity so that the VAR model can be carried out. First-order VAR becomes a model representing the growth of COVID-19 cases in Bandung City and Bandung Regency. The model shows that COVID-19 cases in each region will decrease over time and each region impacts each other. Decreasing cases growth can be caused because people who have been infected and vaccinated have sound immune systems to prevent re-infection. However, prevention still needs to be done to stop the pandemic. Therefore, restrictions on mobility between regions can be used as a strategy to prevent COVID-19 infection.